2012
DOI: 10.1111/j.1442-2042.2012.03184.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial outlet obstruction in rabbits: Duration versus severity

Abstract: Abbreviations & AcronymsObjectives: Oxidative stress is a major etiology of obstructed bladder dysfunction. The major goal of the current study was to correlate the level of oxidative stress with both the severity and duration of obstruction. Methods: A total of 32 New Zealand White rabbits were divided into four equal groups. Groups 1-3 received partial bladder outlet obstructions by standard methods and survived for 4, 8 or 12 weeks. Group 4 received sham surgery at the end of each time period, isolated stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 37 publications
4
24
0
1
Order By: Relevance
“…More specifically, in the current studies the enzyme activities of both SOD and catalase were analyzed in bladders that were grouped by severity and duration to see which bore a stronger correlation to the enzyme activities. We have already shown in these rabbits that the concentrations of both DNP and nitrotyrosine have a stronger correlation with severity than duration . These studies on catalase and SOD should also show if the level of oxidative stress is involved in the activities of these two important anti‐oxidant enzymes.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…More specifically, in the current studies the enzyme activities of both SOD and catalase were analyzed in bladders that were grouped by severity and duration to see which bore a stronger correlation to the enzyme activities. We have already shown in these rabbits that the concentrations of both DNP and nitrotyrosine have a stronger correlation with severity than duration . These studies on catalase and SOD should also show if the level of oxidative stress is involved in the activities of these two important anti‐oxidant enzymes.…”
Section: Introductionmentioning
confidence: 61%
“…Although it is true that the longer the rabbits are obstructed, the higher the level of decompensation, previous studies have shown that obstructed rabbits separated by severity of decompensation rather than by duration of obstruction have a much closer correlation between specific cellular and subcellular dysfunctions than if separated by duration of obstruction alone . In part 1 of the present study, we evaluated the level of oxidative damage in rabbits by two different methods: (i) the rabbits were obstructed for 4, 8 and 12 weeks (duration); and (ii) by severity by separating them into mild, intermediate and severe decompensation . The present study clearly showed that the level of oxidative damage (as measured by the free radical oxidative products nitrotyrosine and DNP) was more closely related to severity of decompensation than to the duration of obstruction.…”
Section: Introductionmentioning
confidence: 97%
“…Microscopic investigations of the bladder wall in these two stages revealed-besides fibroblast hyperplasia and deposition of collagen fibers-smooth muscle cell hypertrophy. Animal studies suggest that bladder emptying in the presence of BOO persists due to increasing detrusor contraction power as a result of structural changes of the bladder wall [2,22]. Additionally, the results of our present study are in line with conclusions from previous studies showing a significant increase of bladder/detrusor wall thickness in symptomatic male patients with BOO [4,5]; therefore, increased detrusor contraction power in patients seems to be generated by increased mass of smooth muscle cells of the bladder wall (detrusor) as well.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress (free radical damage) has been found to be a major factor in a number of major human health problems including heart disease [1][2][3], diabetes [4,5], intestinal diseases [6][7][8], liver disease [9], renal disease [10,11] and obstructive bladder dysfunction [12][13][14][15]. In virtually all of these oxidative stress-linked dysfunctions, antioxidants have proven to be very valuable in their treatment [13,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%